The Syk protein tyrosine kinase can function independently of CD45 or Lck in T cell antigen receptor signaling. - Chu, D H (1996)
The protein tyrosine phosphatase CD45 is a critical component of the T cell antigen receptor (TCR) signaling pathway, acting as a positive regulator of Src family protein tyrosine kinases (PTKs) such as Lck. Most CD45-deficient human and murine T cell lines are unable to signal through their TCRs. However, there is a CD45-deficient cell line that can signal through its TCR. We have studied this cell line to identify a TCR signaling pathway that is independent of CD45 regulation. In the course of these experiments, we found that the Syk PTK, but not the ZAP-70 PTK, is able to mediate TCR signaling independently of CD45 and of Lck. For this function, Syk requires functional kinase and SH2 domains, as well as intact phosphorylation sites in the regulatory loop of its kinase domain. Thus, differential expression of Syk is likely to explain the paradoxical phenotypes of different CD45-deficient T cells. Finally, these results suggest differences in activation requirements between two closely related PTK family members, Syk and ZAP-70. The differential activities of these two kinases suggest that they may play distinct, rather than completely redundant, roles in lymphocyte signaling.